2013
DOI: 10.5005/jp-journals-10013-1142
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Anatomical Variations in the Middle Meatus on Nasal Endoscopy

Abstract: Introduction:The anatomical variations of the lateral wall of nose may create technical difficulties during surgery and increase predisposition for chronic rhinosinusitis (CRS). Various cadaveric and radiological studies have been carried out to identify the variations of critical landmarks in sinonasal anatomy. However, studies analyzing the nasal endoscopic examination of living patients are scarce.Objective: The aim of the study was to compare the anatomical variations in the middle meatus of patients havin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It was seen on left side 24 (23.08%) and on right 08 (7.69%) cases. Joe et al 91 and Bist SS et al 24 reported uncinate variation incidence in 15% and 10% cases respectively. Saxena et al 17 reported a higher incidence.…”
Section: Results and Observationmentioning
confidence: 94%
“…It was seen on left side 24 (23.08%) and on right 08 (7.69%) cases. Joe et al 91 and Bist SS et al 24 reported uncinate variation incidence in 15% and 10% cases respectively. Saxena et al 17 reported a higher incidence.…”
Section: Results and Observationmentioning
confidence: 94%
“…scores have yielded inconsistent results [7][8][9]. Most of these endoscopic scoring systems did not incorporate assessment of the nasal septum or its relationship with the middle turbinate into the scoring system.…”
Section: Various Classificationmentioning
confidence: 99%
“…Concha bullosa (CB) is a pneumatized turbinate, most commonly involving the MNC, and its prevalence varies between 9% in non-rhinosinusitis patients [10] and even up to 76% in patients with chronic rhinosinusitis [37]. It can be divided into six types based on the localization and expansion of its aeration [11].…”
Section: Introductionmentioning
confidence: 99%